The Determinants of Corporate Cash Holdings: Evidence from burgeoning SMEs in China - Li, Hui (2016)
This paper aims at investigating firm-specific determinants in influencing cash holding levels of small and medium sized enterprises (SMEs) of manufacturing industry in China. The targeted firms are selected from Shenzheng Exchange Stock (SZSE), and all of the selected firms are privately owned, because this thesis intends to test the real influence of tested variables on corporate cash holding levels without the influence comes from government and the state. The observation period is from 2010 to 2015. The selected variables which are cash flow, debt structure, firm size, growth opportunity, leverage, liquidity, and profitability. Three theories: trade-off theory, pecking-order theory and free-cash flow theory are used to predict the influence of those independent variables on the corporate cash holding levels. The regression results show that debt structure, leverage, liquidity and profitability are negatively relate to corporate cash holding levels, while cash flow, growth opportunity, and firm size are not significantly influence the cash holding levels of the companies. Besides, the result of the panel data regression shows the existence of autocorrelation of dependent variable, so a one period lagged value of cash is added to the regression model, and the result of autoregressive test shows a positive influence of one period lagged value of cash on the explained variable of cash.